The GBA1 D409V mutation exacerbates synuclein pathology to differing extents in two alpha-synuclein models - Nicole K. Polinski; Terina N. Martinez; Sylvie Ramboz; Michael Sasner; Mark Herberth; Robert Switzer; Syed O. Ahmad; Lee J. Pelligrino; Sean W. Clark; Jacob N. Marcus; Sean M. Smith; Kuldip D. Dave; et al. (The Company of Biologists, 2022)
Heterozygous mutations in the GBA1 gene - encoding lysosomal glucocerebrosidase (GCase) - are the most common genetic risk factors for Parkinson's disease (PD). Experimental evidence suggests a correlation between decreased GCase activity and accumulation of alpha-synuclein (aSyn). To enable a better understanding of the relationship between aSyn and GCase activity, we developed and characterized two mouse models that investigate aSyn pathology in the context of reduced GCase activity. The first model used constitutive overexpression of wild-type human aSyn in the context of the homozygous GCase activity-reducing D409V mutant form of GBA1. Although increased aSyn pathology and grip strength reductions were observed in this model, the nigrostriatal system remained largely intact. The second model involved injection of aSyn preformed fibrils (PFFs) into the striatum of the homozygous GBA1 D409V knock-in mouse model. The GBA1 D409V mutation did not exacerbate the pathology induced by aSyn PFF injection. This study sheds light on the relationship between aSyn and GCase in mouse models, highlighting the impact of model design on the ability to model a relationship between these proteins in PD-related pathology.